The Lived Experience of First-Year University Students: Perspectives, Challenges, and Coping Strategies - Nonkula, Zenande (Journal of Ecohumanism, 2025)
The transition into university presents academic, social, and personal challenges that affect student adjustment and persistence. This study examined the struggles of first-year B.Ed. Humanities students at a South African university, framed by Tinto’s Theory of Student Integration and Schlossberg’s Transition Theory. An interpretivist, qualitative case study design was used, with data collected from 12 purposively sampled students through open-ended Google Form questions, and the data was analyzed thematically. Findings revealed challenges such as heavy workloads, language barriers, limited resources, and insufficient academic feedback. Socially, students reported isolation, difficulty forming peer networks, and balancing academic and personal responsibilities, while personal struggles included stress, financial strain, and mental health concerns. Despite these difficulties, students employed coping strategies including peer support, digital tools, counselling, and self-regulated learning. The study confirms the relevance of academic and social integration to student persistence and highlights the importance of resilience in navigating transitions. It contributes to literature by foregrounding student voices in the South African context and calls for strengthened institutional support, inclusive teaching practices, and expanded mentorship and counselling services to ease first-year adjustment,